Men’s Perceptions and Emotional Responses to Becoming a Caregiver Father: The Role of Individual Differences in Masculine Honor Ideals and Reputation Concerns - Gul, Pelin; Uskul, Ayse K. (Frontiers in Psychology, 2019)
Despite the rising number of men and women in counter-stereotypical roles, primary caregiver fathers and primary breadwinner mothers is a rare role division within families with dependent children. Previous analyses suggest that men’s lower contribution to childcare is due to their lack of interest in performing these tasks, which are primarily influenced by stereotypical expectations and men’s concern with reputation threat. Drawing our predictions from social role theory, shifting standards model, and masculine honor theories, in two studies conducted with British participants (N = 412), we examined people’s judgments of male and female targets who are caregivers and breadwinners, and their evaluative reactions to these targets. We further examined the moderating role of a perceiver characteristic – endorsement of masculine honor ideals – and the role of potential mediators of these relationships. Study 1 showed that male caregivers were rated higher on communal traits than female caregivers, and female breadwinners higher on agentic traits than male breadwinners, indicating gender stereotyping effects through mental shifts to within-sex judgement standards. Studies 1 and 2 showed that men reacted with more negative and less positive emotions to male caregivers (vs. breadwinners) as their endorsement of masculine honor ideals increased. Moderated mediation results of Study 2 further showed that higher endorsement of masculine honor ideals was linked with less positive and more negative emotional reactions to being a caregiver (vs. breadwinner), which was driven by perceived loss of reputation among male friends, whereas lower endorsement of masculine honor ideals was linked with more positive and less negative emotional reactions to being a caregiver (vs. breadwinner), which was driven by perceived gain of wife’s admiration. These findings offer nuanced explanations for why some men may react negatively whereas others may react positively to serving as caregiver fathers, when the stereotyped expectations are still in operation in society.